Identifying and developing the gifts and talents of students with musical ability in New Zealand primary schools : a thesis presented in partial fulfillment of the requirements for the degree of Master of Education, Massey University - Jones, Barry Alfred (Massey University, 2006)
This study was conducted within the New Zealand primary school setting. It sought to address the issue of how to identify musical talent and, once identified, how to nurture that talent. As most primary school teachers are each individually responsible for music education within their classrooms, such teachers need to have the tools to identify, support, motivate and challenge the musically gifted student. This study sought to determine whether Renzulli's (1977) Enrichment Triad Model could be used as a tool to help identify musically talented children and whether it could then be used effectively as a model to implement a gifted music programme. Available literature was explored, looking at explanations and perceptions of musical talent as well as environmental and genetic factors. Renzulli's (1977) Enrichment Triad Model is investigated as are the pros and cons of withdrawal or 'pull-out' programmes. Both quantitative and qualitative data was initially gathered in phase one of the study and the results combined to assist in identifying three musically talented students. Phase one was conducted within three individual school environments. A classroom music creativity programme, a school singing programme, and an after-school keyboard delivery programme. Three students were subsequently identified to participate in phase two. Phase two required the researcher to work individually with these students over a ten week time frame. At the end of the intervention, resulting compositions were performed to a variety of audiences and a Student Product Assessment Form was used to help formerly assess the students' work. This study concluded that the Enrichment Triad Model could he used as an effective model in the delivery of a classroom music programme, the delivery of Types I and II enrichment allowing opportunities to identify musical giftedness while Type III enrichment offered the scope to broaden and develop identified musical talent.
Keywords: New Zealand; Gifted children -- Education (Primary); Musical ability; Music -- Instruction and study